Experiences of family caregivers of patients with terminal disease and the quality of end-of-life care received: a mixed methods study - Martí-García,Celia; Fernández-Alcántara,Manuel; Suárez López,Patricia; Romero Ruiz,Carolina; Muñoz Martín,Rocío; Garcia-Caro,Mᵃ Paz (PeerJ, 2020)
The aim of this study was to analyze the perceptions and experiences of relatives of patients dying from a terminal disease with regard to the care they received during the dying process, considering the oncological or non-oncological nature of the terminal disease, and the place where care was provided (at home, emergency department, hospital room, or palliative care unit). For this purpose, we conducted a mixed-methods observational study in which two studies were triangulated, one qualitative using semi-structured interviews (n = 30) and the other quantitative, using questionnaires (n = 129). The results showed that the perception of relatives on the quality of care was highly positive in the quantitative evaluation but more critical and negative in the qualitative interview. Experience of the support received and palliative measures was more positive for patients attended in hospital in the case of oncological patients but more positive for those attended at home in the case of non-oncological patients.
Keywords: Palliative care; Qualitative; Mixed methods; Bereavement; Relatives; End-of-life care; Caregiver